ANALISIS KUALITAS PELAYANAN PUSKESMAS GAYAMSARI KOTA SEMARANG - Utaminingrum, Ardika Pulung; Mustam, Moch.; Rihandoyo, Rihandoyo (Journal of Public Policy and Management Review, 2015)
Quality of serviceis one measure to assess the public service. One service that is held by public organizations, pubblic health centers Gayamsari Semarang is a public organization of primary health care providers. To determine the quality of public services in public health centers Gayamsari can be seen through the quality of service the level of performance andexpectations based on the relationship between the components of the triangle of balance and dimensions of service quality.The results of this study indicate that the provision of services at public health centers Gayamsari Semarang overall at the level of performance and interest in the category satisfying and important, with an overall average of 2.83 as the level of service performance thresholds are considered satisfactory and the level of interest of the service implementation 3,19 as the limit values that are considered important. The overall average becomes the reference axis of importance and analysis matrix or cartesian diagram.The results of the overall study shows the elements that need to be improved in order to improve the quality of public services in health centers Gayamsari Semarang is clarity care workers, courtesy and friendliness of the clerk and the speed of serviceas a top priority included in quadrant A cartesian diagram and improvements based on a single data element with a view on performance service are still low but is considered important by the community.